Retroperitoneal Lipoblastoma-A Rare Entity - Suhitha Gajanthody (Journal of Clinical and Diagnostic Research, 2018)
Lipoblastomas are uncommon tumours which can achieve enormous size and volumes occurring in young paediatric population predominantly. Retroperitoneal locations of these tumours are very rare and only a few cases have been noted in the literature. In spite of their large size and at times infiltrative nature, they can be surgically excised successfully with low complication rates. They usually present due to pressure effect on adjacent structures or due to mass effect with no malignant potential. We describe a case of large retroperitoneal lipoblastoma and review the current literature and management.